2022
DOI: 10.3390/healthcare10122416
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Bilevel Ventilators to Unintentional Leak: A Bench Study

Abstract: Background: The impact of leaks has mainly been assessed in bench models using continuous leak patterns which did not reflect real-life leakage. We aimed to assess the impact of the pattern and intensity of unintentional leakage (UL) using several respiratory models. Methods: An active artificial lung (ASL 5000) was connected to three bilevel-ventilators set in pressure mode; the experiments were carried out with three lung mechanics (COPD, OHS and NMD) with and without upper airway obstruction. Triggering del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…32 The total leak is a sum of the intentional leak (flow through the leak ports in the mask interface to release exhaled carbon dioxide) and unintentional leak (unwanted leak in the system such as poor mask seal, open mouth with a nasal mask or damaged circuit/tubing). 32 Unintentional leaks can affect the efficacy of NIV therapy and result in poor tolerance, hypoventilation, sleep disturbance and patient-ventilator asynchrony 11,33 The algorithms for VAPS mode from ResMed (iVAPS) and Phillips (AVAPS) are dependent on a reasonable leak to ensure reliable performance and accurate data download. 34 A bench study completed by Fauroux et al 35 in inadequate ventilation, oxygen desaturations, sleep disturbances and exposure to higher inspiratory pressure/pressure support than required.…”
Section: Effects Of Leakmentioning
confidence: 99%
See 1 more Smart Citation
“…32 The total leak is a sum of the intentional leak (flow through the leak ports in the mask interface to release exhaled carbon dioxide) and unintentional leak (unwanted leak in the system such as poor mask seal, open mouth with a nasal mask or damaged circuit/tubing). 32 Unintentional leaks can affect the efficacy of NIV therapy and result in poor tolerance, hypoventilation, sleep disturbance and patient-ventilator asynchrony 11,33 The algorithms for VAPS mode from ResMed (iVAPS) and Phillips (AVAPS) are dependent on a reasonable leak to ensure reliable performance and accurate data download. 34 A bench study completed by Fauroux et al 35 in inadequate ventilation, oxygen desaturations, sleep disturbances and exposure to higher inspiratory pressure/pressure support than required.…”
Section: Effects Of Leakmentioning
confidence: 99%
“…35,36 This can also lead to gastric distention, abdominal discomfort, vomiting and aspiration. 11 Lebret et al 33 demonstrated that in pressure support ventilation with a single limb circuit, the leak pattern affected device performance more than the magnitude of the unintentional leak. A dynamic inspiratory leak resulted in a significant increase in patient ventilator asynchrony with delayed trigger/cycle response, increased work of breathing and decrease in delivered pressure compared to continuous leak of up to 24 LPM.…”
Section: Effects Of Leakmentioning
confidence: 99%